2009
DOI: 10.1111/j.1465-7287.2008.00128.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflation Dynamics in Latin America

Abstract: La serie de Documentos de Investigación del Banco de México divulga resultados preliminares de trabajos de investigación económica realizados en el Banco de México con la finalidad de propiciar el intercambio y debate de ideas. El contenido de los Documentos de Investigación, así como las conclusiones que de ellos se derivan, son responsabilidad exclusiva de los autores y no reflejan necesariamente las del Banco de México.The Working Papers series of Banco de México disseminates preliminary results of economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
10

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 54 publications
3
23
0
10
Order By: Relevance
“…This process continues until to the m breaks and, the dates and the number of the structural break of the model which has the minimum t statistic is taken (Capistrán & Ramos-Francia, 2009). The critical values that are needed to test the null unit root hypothesis are given at Table 1 in the study of Kapetanios (2005).…”
Section: Methodsmentioning
confidence: 99%
“…This process continues until to the m breaks and, the dates and the number of the structural break of the model which has the minimum t statistic is taken (Capistrán & Ramos-Francia, 2009). The critical values that are needed to test the null unit root hypothesis are given at Table 1 in the study of Kapetanios (2005).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, more than one shift of persistence was found when applying Bai–Perron tests for multiple breaks even for the same countries over similar sample periods, and the persistence decreased as a whole, with a remarkable fluctuation in the level when these shifts were taken into account (e.g. Capistrán and Ramos‐Francia () for Mexico and Brazil, and Önder () for Turkey).…”
Section: Literature Reviewmentioning
confidence: 96%
“…Similarly, it is also found that the adoption of IT leads to a fall in inflation persistence for Brazil, Mexico and the 10 largest Latin American economies (Argentina, Bolivia, Brazil, Chile, Colombia, Ecuador, Mexico, Peru, Uruguay and Venezuela) in Chan and Matos (), Chiquiar et al . () and Capistrán and Ramos‐Francia ().…”
Section: Literature Reviewmentioning
confidence: 98%
“…6 Otherwise, these institutions may lose the credibility gained by their favorable track record in the last decades.…”
Section: Experiments 1: Credible Monetary Policymentioning
confidence: 99%